Rancang Bangun Pengaturan Bukaan Choke pada Genset Hybrid (Bensin dan Bioetanol) - Ridwan Baharta; Bastaman Syah (Jurnal Ilmiah Teknik Pertanian - TekTan, 2014)
Until recently, generator available in the market, generally gasoline or LPG. Conversion of gasoline to fuel bio-ethanol requires some adjustments.The research conducted was  a further development of research Nurjan Didik Purwanto in 2011. The research was focused on adjustment of airand fuel ratio after the fuel in the generator set was replaced with bioethanol. Bioethanol has a higher octane rating than gasoline, but it has a lower calorific value than petrol. With this condition, it is necessary to attempt to increase the ratio of air and fuel to be more "fat " to regulate the entry of air through the carburetor. Settings ratio of fuel and air is done by adjusting the carburetor choke openings. This setting restores the stability of the engine, the same as using premium gasoline.This study primarily aims to expand the use of renewable energy, especially for the implementation of electric power for households.The results of this research  has been successfully realized by using a Timer Switch AC, 12 Volt DC timer switch, solenoid valve (solenoid valve), and actuators. Aperture choke1/3 on the use of bio-ethanol fuel produces almost simillar to  the engine speed compare to it when  using gasoline. Fuel consumption of bioethanol is 40% more than the use of  gasoline. Keywords: choke, gasoline, bio ethanol